ANALYSIS OF THE EFFECT OF ADHESIVES ON PAPERS CONTAINING POLYESTER (LAVSAN) FIBRE WASTE (Conferencea, 2023)
In the article, high-strength paper samples are analysed during the production process of paper containing polyester (lavsan) fibre waste, including the introduction of adhesives into the paper cellulose together with synthetic waste fibres, the influence of selected adhesives on the physical-mechanical and printing properties of paper.